CELERY LEAF BOILED WATER EXTRACT TO LOWER BLOOD PRESSURE IN ELDERLY WITH HYPERTENSION - Yuliawan, Deny; I'ana Aulia Andari (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2025)
Introduction: Hypertension is a major risk factor that contributes to early cardiovascular morbidity and mortality worldwide. Management of hypertension is necessary to include pharmacological and non-pharmacological interventions. An alternative non-pharmacological therapy to minimizing the burden of the patients, the families, and also the government. Innovation by Evidence-based which is the use of celery leaf extract aimed at blood pressure management in hypertensive patients. the purpose of the community services has integrated community nursing practice and apply celery leaf boiled water for lowering blood pressure. Methods: The implementation method involves carrying out a pre-treatment examination in the form of checking blood pressure and filling out a form, then a demonstration of making boiled celery leaf extract. Participants were given instructions to make the extract at home and consume it 2 times per day after eating for 7 days. During implementation, participants were directed to fill out a form to schedule their routine consumption of boiled celery leaf extract. Post-treatment data was collected after 7 days of implementation. Results: The results showed that there was a difference in pre- and post-treatment systolic pressure p-value 0.0001, there was a difference in pre- and post-treatment diastolic pressure p-value 0.001. Conclusion: The number of categories of pre and post treatment blood pressure measurements showed positive results. The boiled celery leaf extract has shown positive results for lowering blood pressure in elderly participants. Furthermore, this innovation program requires optimization of comprehensive support from various part or stakeholders, so that the benefits can be felt by the wider community.